Does Managerial Ability Affect Earnings Quality? - Nabiilah; Lastiati, Anies (Adpebi Science Series, 2024)
This research aims to evaluate the influence of managerial ability on earnings quality. Moreover, it also tests whether institutional ownership is able to moderate the relationship between managerial ability and earnings quality. This quantitative research is conducted using data from manufacturing companies listed in the Indonesian Stock Exchange 2021-2022. The research results show that there is a significant influence between managerial ability and earnings quality in a negative direction.